Camel's milk concentrate inhibits streptozotocin induced diabetes. (December 2018) - Ismail, Tariq; Ahmad, Zeshan; Sestili, Piero; Hussain, Majid; Akram, Kashif; Ismail, Amir; Akhtar, Saeed
Abstract: The hypoglycemic effect of different forms of camel milk, i.e., pasteurized (CM), powdered (PcM) and evaporated (EcM) in a rat model of chemically-induced diabetes was studied. Diabetes was induced by a single intraperitoneal injection of streptozotocin (65 mg/kg b.w.). Diabetic rats were supplemented with CM ( ad lib ), PcM (18.4 g/kg b.w.) and EcM (12.2 g/kg b.w.) for a period of 21 days. EcM feeding was found to normalize serum glucose, triglycerides, LDL-cholesterol, serum creatinine, bilirubin, uric acid and liver enzymes levels. On the other hand, CM and PcM feeding did not reduce the levels of serum glucose, lipids, and kidney and liver function markers to their normal values. Accordingly, histopathological examinations also showed visible signs of pancreatic β-cells repair with mild cellular atrophy in EcM fed diabetic rats. The data suggested that low temperature processed milk-concentrate consumption may represent a complimentary approach to maintaining normal serum glucose levels and securing optimal renal and hepatic function with diabetes.